2017
DOI: 10.1002/jcla.22322
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of Clauss and prothrombin time‐derived methods for determining fibrinogen concentrations: Screening for congenital dysfibrinogenemia

Abstract: The combined use of Clauss and PT-derived methods for determining fibrinogen concentrations improves the efficiency of screening for congenital dysfibrinogenemia, as the fibrinogen PT-derived/Clauss ratio has high sensitivity and specificity in diagnosis of congenital dysfibrinogenemia. This ratio could serve an important screening tool for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
(21 reference statements)
0
32
0
2
Order By: Relevance
“…Routine coagulation tests such as TT and functional Fg concentration or Fg concentration tests are useful for the diagnosis of CD. Our recent study showed that the sensitivity and specificity of these tests to CD detection were 100% when Fg (PT‐derived method)/Fg (Clauss method) was >1.43 . However, these routine tests cannot completely assess the coagulation function in the human body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine coagulation tests such as TT and functional Fg concentration or Fg concentration tests are useful for the diagnosis of CD. Our recent study showed that the sensitivity and specificity of these tests to CD detection were 100% when Fg (PT‐derived method)/Fg (Clauss method) was >1.43 . However, these routine tests cannot completely assess the coagulation function in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study showed that the sensitivity and specificity of these tests to CD detection were 100% when Fg (PT-derived method)/Fg (Clauss method) was >1.43. 19 However, these routine tests cannot completely assess the coagulation function in the human body. TEG is a method that assesses the global haemostatic state and fibrinolytic function based on the trace reflecting Receiver operating characteristics (ROC) analysis was performed to calculate sensitivity, specificity and area under the ROC curve (AUC) with the associated P value.…”
Section: Teg In Clinical Practicementioning
confidence: 99%
“…The first step should include APTT and PT as well as a functional assessment of the fibrinogen level by the Clauss method and an antigenic measurement. If antigenic measurement is not possible, as a second‐choice method, a PT‐Fg/Clauss ratio may be used . The thrombin time and the reptilase time are frequently prolonged but they are not required for the diagnosis of CFD.…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Essas curvas de referência são resultantes da coagulação, utilizando diluições em série, de plasma com concentração de fibrinogênio conhecida. [63][64][65][66] O resultado do teste é obtido em g/l. Seu tempo de resposta é de aproximadamente 40 min.…”
Section: Método De Claussunclassified
“…[41][42][43] No método de Clauss, a diluição do plasma destina-se a limitar a interferência dos produtos de degradação do fibrinogênio, das altas concentrações de anticoagulantes (por exemplo, heparina) ou da polimerização anormal de fibrina induzida por defeitos de fibrinogênio, que podem resultar em valores mais baixos de concentrações de fibrinogênio determinadas pelo teste. 63,65 O ensaio de Clauss é considerado o teste padrão para a medição da concentração plasmática de fibrinogênio, 41,43,64 e nenhum outro teste é substituto adequado para essa determinação dos níveis de fibrinogênio. 42…”
Section: Método De Claussunclassified